CL-705G: a novel chemical Kir6.2-specific KATP channel opener - Gando, Ivan; Becerra Flores, Manuel; Chen, I.-Shan; Yang, Hua-Qian; Nakamura, Tomoe Y.; Cardozo, Timothy J.; Coetzee, William A. (Frontiers in Pharmacology, 2023)
Background: KATP channels have diverse roles, including regulation of insulin secretion and blood flow, and protection against biological stress responses and are excellent therapeutic targets. Different subclasses of KATP channels exist in various tissue types due to the unique assemblies of specific pore-forming (Kir6.x) and accessory (SURx) subunits. The majority of pharmacological openers and blockers act by binding to SURx and are poorly selective against the various KATP channel subclasses. Methods and Results: We used 3D models of the Kir6.2/SUR homotetramers based on existing cryo-EM structures of channels in both the open and closed states to identify a potential agonist binding pocket in a functionally critical area of the channel. Computational docking screens of this pocket with the Chembridge Core chemical library of 492,000 drug-like compounds yielded 15 top-ranked ‘hits’, which were tested for activity against KATP channels using patch clamping and thallium (Tl+) flux assays with a Kir6.2/SUR2A HEK-293 stable cell line. Several of the compounds increased Tl+ fluxes. One of them (CL-705G) opened Kir6.2/SUR2A channels with a similar potency as pinacidil (EC50 of 9 µM and 11 µM, respectively). Remarkably, compound CL-705G had no or minimal effects on other Kir channels, including Kir6.1/SUR2B, Kir2.1 or Kir3.1/Kir3.4 channels, or Na+ currents of TE671 medulloblastoma cells. CL-705G activated Kir6.2Δ36 in the presence of SUR2A, but not when expressed by itself. CL-705G activated Kir6.2/SUR2A channels even after PIP2 depletion. The compound has cardioprotective effects in a cellular model of pharmacological preconditioning. It also partially rescued activity of the gating-defective Kir6.2-R301C mutant that is associated with congenital hyperinsulinism. Conclusions: CL-705G is a new Kir6.2 opener with little cross-reactivity with other channels tested, including the structurally similar Kir6.1. This, to our knowledge, is the first Kir-specific channel opener.